VD_FINDINFO HC / 2015 / 1025 vom 1. Dezember 2015 - VD Tribunal cantonal (2015)
SIGNATURE, SIGNATURE INDIVIDUELLE, ABUS DE DROIT, EXPULSION DE LOCATAIRE, PROTECTION DES LOCATAIRES, DEMEURE, SOMMATION | 257d CO, 257 CPC (CH)